2016
DOI: 10.1017/s0007114516000283
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of dietary energy misreporting among European adolescents: the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study

Abstract: This study examined the correlates of dietary energy under-reporting (UR) and over-reporting (OV) in European adolescents. Two selfadministered computerised 24-h dietary recalls and physical activity data using accelerometry were collected from 1512 adolescents aged 12·5-17·5 years from eight European countries. Objective measurements of height and weight were obtained. BMI was categorised according to Cole/International Obesity Task Force (IOTF) cut-off points. Diet-related attitudes were assessed via self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 46 publications
7
59
0
Order By: Relevance
“…underreporting, is a well-known general phenomenon, but has not been studied in elite male wrestlers (31)(32)(33). The 19% underreporting is not dissimilar to what has been reported in many other studies, but is larger than would be expected based on BMI alone (34) and thus may reflect the effects of worry about weight gain (35). Although many dietary energy studies display underreporting, self reports are still commonly used for estimating EI in athletes.…”
Section: Discussionmentioning
confidence: 93%
“…underreporting, is a well-known general phenomenon, but has not been studied in elite male wrestlers (31)(32)(33). The 19% underreporting is not dissimilar to what has been reported in many other studies, but is larger than would be expected based on BMI alone (34) and thus may reflect the effects of worry about weight gain (35). Although many dietary energy studies display underreporting, self reports are still commonly used for estimating EI in athletes.…”
Section: Discussionmentioning
confidence: 93%
“…Biased reporting is another disadvantage that may include misinterpreting or misunderstanding of the questions, lack of motivation and not paying attention while filling out the questionnaire. A study on European adolescents found that weight status and psychosocial weight-related factors are the major correlates of misreporting of dietary energy [70]. Also, the questions used to measure eating habits were limited to information on the consumption of five food items (fruit, vegetables, soft drinks, sweets and breakfast) and did not measure the quantities of food eaten and whether children met the dietary recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Most dietary screeners use recall of the past day's intake (e.g., 24-h recall) or usual food/beverage consumption frequency [NCCOR, 2017]. These instruments require recall of behavior, which is cognitively challenging [Johnson, 1983], time intensive, and likely biased by misreporting, particularly among heavier children [Bel-Serrat et al, 2016]. Alternatively, asking about food/beverage preference is cognitively simpler, quicker and often less biased.…”
Section: Introductionmentioning
confidence: 99%